The Current Situation And Problems of Migrant Children’s Education In Henan Province of China: An Empirical Analysis From The Perspective of Home-School-Community - Zhang, Danhui; Phakamach, Phongsak (Jurnal Edusci, 2024)
Family education, school education, and social education play different roles in people's growth, both educational roles and mutual coordination and integration. From the perspective of family, school, and community cooperation, this study deeply discusses the current situation and countermeasures of migrant workers' children's education in Zhengzhou. The education status of migrant workers' children in Zhengzhou City is investigated by means of questionnaires, mainly from four dimensions: the basic situation of migrant workers' children, their family situation, their school situation and their own feelings.